2020
DOI: 10.2147/dhps.s254644
|View full text |Cite
|
Sign up to set email alerts
|

<p>Chemotherapy-Related Adverse Drug Reaction and Associated Factors Among Hospitalized Paediatric Cancer Patients at Hospitals in North-West Ethiopia</p>

Abstract: Background One of the prevalent treatment modalities for cancer is chemotherapy. Adverse drug reactions, however, are becoming the world’s major public health problem. More than half (54.5 percent) of cancer patients need hospitalization for further management, in addition to the increased health-care costs of treatment. The aim of this study was to evaluate adverse drug reactions associated with chemotherapy and related factors in hospitalized paediatric cancer patients in Ethiopia’s north-west h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 36 publications
0
19
2
Order By: Relevance
“…34 Our study revealed that adult cancer patients who received platinum agents were two times likely to develop nephrotoxicity than those who received other treatment regimens, a finding similar to other studies done in Switzerland, 31 Canada, 35 Brazil, 36 and Ethiopia. 37 The high prevalence of nephrotoxicity among adult cancer patients who received platinum agents may be due to the preventive strategies used where hydration with normal saline and administration of magnesium sulphate were the preventive measures for nephrotoxicity. Other strategies such as administration of mannitol should be considered while developing a pharmaceutical care plan for such patients.…”
mentioning
confidence: 99%
“…34 Our study revealed that adult cancer patients who received platinum agents were two times likely to develop nephrotoxicity than those who received other treatment regimens, a finding similar to other studies done in Switzerland, 31 Canada, 35 Brazil, 36 and Ethiopia. 37 The high prevalence of nephrotoxicity among adult cancer patients who received platinum agents may be due to the preventive strategies used where hydration with normal saline and administration of magnesium sulphate were the preventive measures for nephrotoxicity. Other strategies such as administration of mannitol should be considered while developing a pharmaceutical care plan for such patients.…”
mentioning
confidence: 99%
“…Some pediatric studies found that a high proportion of reports about ADRs in males ( 21 , 22 ). In our research, nearly three-fifths of the reports were related to males (n = 267).…”
Section: Discussionmentioning
confidence: 99%
“…Using the research strategies defined previously, 7,712 studies were retrieved from PubMed database. Forty articles were considered relevant for eligibility and finally, considering inclusion and exclusion criteria, 14 studies were included in the systematic review (Collins et al, 1974;Mitchell et al, 1988;Queuille et al, 2001;Le et al, 2006;Gallagher et al, 2012;Posthumus et al, 2012;Barrett et al, 2013;Call et al, 2014;Langerová et al, 2014;Makiwane et al, 2019;Dittrich et al, 2020;Joseph et al, 2020;Morales-Ríos et al, 2020;Workalemahu et al, 2020). Due to the characteristics of studies found, a meta-analysis was considered not feasible to be carried out.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 14 studies included, six were carried out in pediatric oncology and hematology patients, and eight were carried out in general pediatrics and included a clear pediatric oncohematology subgroup. Four studies (Collins et al, 1974;Mitchell et al, 1988;Queuille et al, 2001;Le et al, 2006) were published before 2010, and 10 studies (Gallagher et al, 2012;Posthumus et al, 2012;Barrett et al, 2013;Call et al, 2014;Langerová et al, 2014;Makiwane et al, 2019;Dittrich et al, 2020;Joseph et al, 2020;Morales-Ríos et al, 2020;Workalemahu et al, 2020) were published later.…”
Section: Resultsmentioning
confidence: 99%